Introduction. The history of the talking machines raises foundational questions on humanity and reminds us on the power of imagination - Pertti Grönholm (Turun yliopisto, 2022)
Tutkimushankkeen verkkosivun yleistajuinen johdantoartikkeli.
Talking Machines